KARAKTERISTIK IBU DAN POST NATAL TREATMENT (PNT) BERHUBUNGAN DENGAN TERJADINYA POSTPARTUM BLUES IBU NIFAS - Yuliyanik, Yuliyanik (Universitas Tribhuwana Tunggadewi, 2019)
This study aimed at examining the occurrence of postpartum blues in postpartum mothers. Post partum blues is categorized as a mild mental disorder syndrome for it is often ignored so that it is undiagnosed and not treated as it should, which finally leads to a difficult and unpleasant problem that may create feelings of discomfort for women who experience it. The study is intended to prevent the occurrence of Post partum blues in postpartum mothers. Post Partum Blues can be prevented by doing ANC and Post Natal Treatment routinely. Post Natal Treatment is a series of treatments performed specifically for postpartum mothers, which include massage, breast care, oxytocin massage, postpartum spa and full-blooded face. The research employed observational methods. The population of all puerperal mothers was 20 people, using total sampling. Data is obtained from primary data and secondary data, then the data is processed using SPSS 16 with chi square test. The conclusion of the value of p = 0.01 is that there is a relationship between the characteristics of postpartum mothers and PNT with the occurrence of postpartum blues. Age, education and occupation of postpartum mothers are associated with the insidence of postpartum blues. PNT that had been received by postpartum mothers was also related to the insidence of postpartum blues. Researcher's suggestion is for postpartum mothers to carry out ANC and PNT routinely to prevent the occurrence of post partum blues.